Seeing the Ice. An Overview of Alpine Glacier Tourism Sites, Between Post- and Hyper-Modernity - Emmanuel Salim; Christophe Gauchon; Ludovic Ravanel (Revue de Géographie Alpine)
Glaciers have been popular tourist attractions for almost two centuries. However, current climate change is now posing a new threat. In this context, this paper aims to question the tourism forms which are currently identifiable within Alpine glacier tourism sites. An inventory carried out on an Alpine scale shows that different tourist practices (contemplation, visit of ice caves, recreational activities, environmental education, and luxury) can coexist. The analysis of the way various sites function demonstrates that these practices can be related to the different forms of tourism that exist in the scientific literature: modern, post-modern and hyper-modern tourism. The coexistence of these forms of tourism at glacier sites reveals six possible combinations, i.e. six types of sites: contemplative, experiential, recreational, interpretative, premium and distinctive. Spatial analysis also shows that the premium and distinctive sites are mainly located around the major Alpine tourist destinations (Chamonix, Zermatt and Grindelwald), while the others are more homogeneously distributed. These results raise questions about the way in which these sites was and will develop and the role climate change plays, both of which constitute potential research topics for the future.